Review and Challenges in the Geophysical Mapping of Coal Mine Water Structure - Chuantao Yu; Weiying Chen; Xi Zhang; Kangxin Lei (Geofluids)
Generally, the water-bearing structures of coal mines mainly include coal seam, roof, coal seam, floor, and goaf, while the main water-conducting structures include faults, collapsed columns, and collapsed goaf areas. The most commonly used methods for the detection of the above structures include the seismic method, high-density electrical method, controlled source audio-frequency magnetotelluric method, and transient electromagnetic method. Theoretically, the seismic methods have a higher resolution, which can be used to determine the targets’ geometry, but unable to determine whether the target is filled with water, while the electromagnetic methods are capable of this, although with lower resolution. Therefore, it is necessary to adopt the comprehensive geophysical prospecting in the actual field measurement of the coal mine water to guarantee the detection accuracy. Based on this, in the passage, first, we introduced the characteristics of the water-bearing and water-conducting structures and then analyzed the detection results of different methods by examples. Finally, we pointed out that, first, it is essential to develop the mine or airborne methods for the sake of convenience; and second, it is time that we adopt three-dimensional detection technology, multisource and multiresolution detection technology, and electromagnetic big data technology for high accuracy.